Microwave-Assisted Extraction of Polyphenol Content from Leaves of Tristaniopsis merguensis Griff. - Robby Gus Mahardika; Occa Roanisca (ASEAN Journal of Chemical Engineering, 2020)
Tristaniopsis merguensis Griff. is a species of the Myrtaceae family and has been widely used by people of Bangka Belitung as a traditional medicine to reduce cholesterol, gastric pains, and improve cardiac performance. Extraction methods are the crucial efficacy of herbal medicine. The conventional method, like maceration, takes a long time. In this study, the leaves of Tristaniopsis merguensis were extracted using Microwave-Assisted Extraction (MAE) to reduce extraction time. The extraction using MARS (Microwave Accelerated Reaction System) 6 by CEM Corporation with time variation times of 5, 10, 15, 30 min with temperature of 60, 80, 100oC at 1200 W. The yield using acetone extraction of Tristaniopsis merguensis leaves increases with time and temperature. The extraction dependent on solvent extraction, polar solvent like ethanol, and methanol were higher than semi-polar solvents like acetone and ethyl acetate. The polyphenol content of acetone extract using MAE (10 min, 80oC) was found to be 234.67 mg Gallic Acid Equivalent per gram (GAE/g); it was higher than acetone extract using maceration. The phytochemical results show there are no difference in the active compound using MAE and maceration, i.e. alkaloids, tannin, and flavonoids. Yield extraction, time, and phytochemical results of MAE are more favorable than a maceration.